Presentation and validation of the Services Excellence Modern Management Model "GEMSES" - Pérez-Pérez, Carlos (2021)
Management models with demonstrated usefulness are consistent and powerful tools helpful to transform organizations. Objectives: first, to describe the Services Excellence Modern Management Model (GEMSES) as a choice for excellence-oriented management in services, and to present results of the validation processes. Methods: It was a study based on documentary research to build the proposal and combined qualitative and quantitative approaches to validate the model. Results: GEMSES is a comprehensive model based on a combination of methodologies and the Systemic Theory. General content validity (coefficient= 0.94) and VRC’ (0.75) were calculated to establish the validity of its components. For model application validity, it was used in a health service center. Results showed an impact of 62% on the management level. The management level changed from 34% to 94%. The components with a higher impact percentage were value chain, strategy implementation, and research (100% each).  Training (94%) and management models (83%) also showed high percentages. Conclusion: GEMSES is a consistent, powerful, and innovator model which validity has been proven in terms of content and use. This model contributes to raising excellence in management, taking as a starting point the clients’ needs and pursuing the goal of their satisfaction.